Augmented Reality Media in Teaching English for Young Learner - Syamsinar Syamsinar (Jurnal Studi Guru dan Pembelajaran, 2022)
The development of technology is growing rapidly. This affects several sectors of life. One of them is in the education sector. Teachers are accustomed to use information and communication technology (ICT) tools such as computers and smartphones in learning. Especially in early childhood learning where the use of smartphones can motivate students in learning. Therefore, the researcher used smartphone in learning by using Augmented Reality as a Media. The Augmented reality media is in the form of books. The books are ABC fun with Mickey and 123 counting fun with Mickey. This research used qualitative research. The data were collected by using classroom observation and interview. The obtained data were analyzed in four major namely data collection, data display, data condensation and draw conclusion. Based on the result of observation, the students were active in learning English by using augmented reality media. They were very excited because it was a new experience for them in learning by using this media. Beside that, it was very helpful because the media was interactive and students were able to learn while playing which really supports student learning, especially for young learner. They highly recommend the use of this media because it is very interesting for students